Empathy, quality of life and occupational burnout among medical students - Shoaleh Bigdeli; Seyed Kamran Soltani Arabshahi; Atefeh Zabihi Zazoly; Azam Norouzi; Nahid Ahmadian Yazd; Agha Fatemeh Hosseini (Tabriz University of Medical Sciences, 2021)
Background: Empathy, quality of life, and occupational burnout are essential factors in medical sciences that affect the physicians' and patients' communication. Therefore, the purpose of this study was to investigate the association of these three factors among medical students. Methods: This descriptive correlational study was conducted among medical internship students. Participants were selected by using simple random sampling. The Jefferson Empathy Questionnaire, the WHO Quality of Life Questionnaire, and the Maslach Burnout Questionnaire were used for data collection. Data were analyzed using t test, Kruskal-Wallis, analysis of variance (ANOVA), and Pearson's correlation coefficient. Results: A total of 167 students completed the questionnaires. The association of empathy and occupational burnout (P=0.005, r=-0.414) and between the quality of life and occupational burnout (P=0.005, r=-0.446) were both significantly negative. Independent t test showed the mean score of occupational burnout was significantly higher in male students than females. It was also significantly higher in married students than single (P<0.05). The results of the KruskalWallis test showed no statistically significant difference among the quality of life of different ethnic groups (P>0.05). One-way ANOVA showed that there was a statistically significant difference between the ethnic groups in terms of occupational burnout (P<0.05) Conclusions: The association of empathy and quality of life with occupational burnout was negative. The highest quality of life was related to older students. Among all of the studied variables, married status, ethnicity, and sex were most associated with occupational burnout where married and male students had the highest burnout.